2013
DOI: 10.1111/jth.12117
|View full text |Cite
|
Sign up to set email alerts
|

Platelet dysfunction associated with the novel Trp29Cys thromboxane A2 receptor variant

Abstract: sem P, The UK GAPP Study Group. Platelet dysfunction associated with the novel Trp29Cys thromboxane A 2 receptor variant. J Thromb Haemost 2013; 11: 547-554. Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…For example, it can be used to resolve IPDs with digenic roots as illustrated by observations in TBXA2R: 4 reports describe LOF variants of TBXA2R in patients with platelet defects as a dominant finding. 78,[116][117][118] Although heterozygosity for the TBXA2R variants correlated with the platelet defect in these carriers, there was no association with bleeding problems. It was noted that a potential second genetic factor would be required to cause bleeding.…”
Section: Protein-protein Interaction Networkmentioning
confidence: 85%
“…For example, it can be used to resolve IPDs with digenic roots as illustrated by observations in TBXA2R: 4 reports describe LOF variants of TBXA2R in patients with platelet defects as a dominant finding. 78,[116][117][118] Although heterozygosity for the TBXA2R variants correlated with the platelet defect in these carriers, there was no association with bleeding problems. It was noted that a potential second genetic factor would be required to cause bleeding.…”
Section: Protein-protein Interaction Networkmentioning
confidence: 85%
“…This interaction causes a wide variety of biological effects, including platelet aggregation. To this end, TPR's clear role in normal hemostasis is supported by the finding that “patients” have a bleeding disorder as a result of a point mutation in the receptor protein 14, 15, 16. On the other hand, upregulated signaling through TPR has been implicated in the pathogenesis of multiple cardiovascular and thrombosis‐based diseases 17, 18, 19, 20.…”
Section: Introductionmentioning
confidence: 99%
“…Two further function-disrupting TBXA2R variants predicting amino acid substitutions within TMD1 have also been characterized (Figure 1; (7,8)). Both of these variations reduce TPα receptor expression at the cell surface, suggesting an important role for TMD1 in the regulation of anterograde receptor traffic.…”
mentioning
confidence: 99%
“…Both of these variations reduce TPα receptor expression at the cell surface, suggesting an important role for TMD1 in the regulation of anterograde receptor traffic. The first of these variants, a Trp29Cys substitution, was identified in a patient with abnormal postsurgical bleeding and reduced TPα receptor-mediated platelet activation responses (7). Ligand-binding studies indicated a reduction in both surface receptor expression and ligand-binding affinity with the Trp29Cys variant.…”
mentioning
confidence: 99%
See 1 more Smart Citation